2021
DOI: 10.1007/s12015-021-10156-4
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐articular Injection of PDGF-BB Explored in a Novel in Vitro Model Mobilizes Mesenchymal Stem Cells From the Synovium Into Synovial Fluid in Rats

Abstract: BackgroundDrugs that can induce mesenchymal stem cell (MSC) mobilization from synovium into synovial uid will enable regenerative medicine in joints without use of exogenous MSCs. An in vitro synovial MSC migration model had previously been developed for screening but had problems in practical application. We herein developed a novel in vitro model, explored cytokines for synovial MSC mobilization with this model, and veri ed whether MSCs in synovial uid increase following intra-articular injection of the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Histological evaluation of the rat knee joints revealed that synovitis was most strongly correlated with colony number. This nding was consistent with our previous ndings that in ammatory cytokines enhanced the migration ability of synovial MSCs and that synovium-resident MSCs appeared to mobilize into the SF in response to synovitis [17]. Immunostaining of the synovium to identify events responsible for changes in SF-MSCs demonstrated a signi cant correlation between the CD68-positive area in the synovium and the SF-MSC colony number and area.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Histological evaluation of the rat knee joints revealed that synovitis was most strongly correlated with colony number. This nding was consistent with our previous ndings that in ammatory cytokines enhanced the migration ability of synovial MSCs and that synovium-resident MSCs appeared to mobilize into the SF in response to synovitis [17]. Immunostaining of the synovium to identify events responsible for changes in SF-MSCs demonstrated a signi cant correlation between the CD68-positive area in the synovium and the SF-MSC colony number and area.…”
Section: Discussionsupporting
confidence: 92%
“…The numbers of endogenous MSCs will need to be increased to achieve endogenous tissue regeneration. We previously demonstrated that intraarticular injection of PDGF-BB effectively mobilized synovial MSCs into the SF [17]. Baboolal et al reported a mechanical method to increase SF-MSCs that involved agitation of the synovium during arthroscopy [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to suppressing T cell proliferation, PDGF also increases MSC migration and proliferation. Endo et al ( 53 ) found that cell migration was increased in vitro when synovial MSCs were cultured in media supplemented with PDGF-BB. They also found that intra-articular PDGF-BB treatment increased MSC proliferation and colony-forming potential ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Endo et al ( 53 ) found that cell migration was increased in vitro when synovial MSCs were cultured in media supplemented with PDGF-BB. They also found that intra-articular PDGF-BB treatment increased MSC proliferation and colony-forming potential ( 53 ). Although beyond the scope of this study, increased levels of PDGF-BB in PL containing medias could provide an advantage when injecting MSCs intra-articularly by not only improving the function of injected MSCs but also recruitment and proliferation of endogenous MSCs already present within the joint.…”
Section: Discussionmentioning
confidence: 99%